Synthesis and Characterization of Novel Surfactants based on 2‐Hydroxy‐4‐(Methylthio)Butanoic Acid Part 3: Microemulsions from Nonionic Sulfoxide Ester Surfactants. Issue 1 (21st October 2018) - Shahrashoob, Zahra; Yu, Guangzhe; Long, Scott; Grady, Brian P.; Harwell, Jeff; Arhancet, Graciela
Abstract: In this work, ester sulfoxide (ESO) surfactants based on 2‐hydroxy‐4‐(methylthio) butyric acid are shown to have temperature‐sensitive microemulsion phase behaviors. Both C10 (C10 ESO) and C12 (C12 ESO) surfactants studied contained one sulfoxide unit in the structure. Phase inversion temperatures (PIT) and interfacial tensions (IFT) between water‐rich and oil‐rich phases have been measured for ternary systems of water, oil, and sulfoxide surfactants. Hydrophilic–lipophilic deviation (HLD) parameters of these surfactants were obtained by fitting the experimental data to a semiempirical HLD equation. The characteristic surfactant parameter and temperature sensitivity of C10 ESO and C12 ESO surfactants were obtained and compared with similar ethoxylated alcohol surfactants. By comparing the characteristic parameters of these surfactants with those of ethoxylated alcohol surfactants, it was shown that one sulfoxide ester moiety is equally hydrophilic as approximately 5 ethylene oxide groups. The temperature sensitivity of the ESO was roughly a factor of four less than ethoxylated surfactants based on the temperature coefficient of the HLD equation.